Individual Protective Covers (IPCs) for Young Tree Protection from the HLB Vector, the Asian Citrus Psyllid - Fernando Alferez; Ute Albrecht; Susmita Gaire; Ozgur Batuman; Jawwad Qureshi; Mongi Zekri (EDIS)
Psyllid exclusion is the most effective strategy to keep citrus trees free from HLB. Individual protective covers (IPCs) are a novel strategy based on psyllid exclusion of individual trees using a protective mesh bag. This new 3-page publication summarizes the knowledge we have accrued from our 3-year-long field studies using the IPC system and provides recommendations that can help with effective use of this technology. By F. Alferez, U. Albrecht, S. Gaire, O. Batuman, J. Qureshi, and M. Zekri. https://edis.ifas.ufl.edu/hs1425